THE INTRODUCTION OF PANICOID CROPS IN THE REPUBLIC OF NORTH OSSETIA - ALANIA - S. A. Bekuzarova; G. V. Lushchenko (Труды по прикладной ботанике, генетике и селекции)
Each particular crop has a number of features that lead to changes in the use of new substances and also impact productivity and product quality. From this point of view, panicoid grass crops deserve much attention, especially when introduced in the mountain and foothill regions of the Republic of North Ossetia - Alania where poultry husbandry is well developed. Setaria italica subsp. moharicum Alef., Echinochloa frumentacea Link, Setaria italica subsp. maxima Alef. have been introduced at the North Caucasus Research Institute of Mountain and Foothill Agriculture as new crops for the republic. The goal was to improve their biological potential by applying innovative technologies. To achieve this, the sowing time and methods, as well as reproductive features of these crops were studied. Sowing and harvesting dates have been varied, and peculiarities of developmental biology taken into account. During the years of research, Echinochloa frumentacea Link has been found resistant to abiotic stresses in the foothill areas of the republic. Also, the optimal sowing time, seeding rate, plant density and survival rate, as well as 1000 seeds weight have been determined.